Evaluating a workshop model effectiveness for faculty training in Team-Based Learning (Research, Society and Development, 2021)
This study aimed to evaluate the effectiveness of a teacher qualification workshop in Team-Based Learning (TBL) with medical professors from a private higher education institution in Belém/PA/Brazil. It was an action research through questionnaires to assess the prior knowledge of teachers about the TBL methodology before and after the proposed workshops. The results showed that the rate of correct answers regarding the number of steps in the methodology rose from 15.62% to 96.9%. Regarding the stages of the TBL, the correct answers rose from 3.12% to 87.5%. As for the time allocated for each stage, the correct answers rose from 3.12% to 68.7%. It is noteworthy that 96.9% of respondents reported understanding the benefits of TBL after the workshops held and, of these, 53.12% did not understand it before. This allows us to state that the workshops, in addition to qualifying teachers, were also able to sensitize them about the benefits of this educational strategy in the teaching-learning process. Such data point to the success of the workshops, thus allowing the participants to apply this teaching strategy with greater security and assertiveness in their teaching routine. It was found, therefore, that the educational technology developed is a valid tool for implementation in the development of teachers in other educational institutions. It is hoped that this work can contribute to learning about TBL and can make it, in order to encourage teachers and institutions to introduce this valuable tool in their realities.